From Photon Beam to Accelerated Particle Beam: Antimetastasis Effect of Combining Radiotherapy With Immunotherapy - Ma, Liqiu (Frontiers in Public Health, 2022)
Cancer is one of the major diseases that seriously threaten the human health. Radiotherapy is a common treatment for cancer. It is noninvasive and retains the functions of the organ where the tumor is located. Radiotherapy includes photon beam radiotherapy, which uses X-rays or gamma rays, and particle beam radiotherapy, using beams of protons and heavy ions. Compared with photon beam radiotherapy, particle beam radiotherapy has excellent dose distribution, which enables it to kill the primary tumor cells more effectively and simultaneously minimize the radiation-induced damage to normal tissues and organs surrounding the tumor. Despite the excellent therapeutic effect of particle beam radiotherapy on the irradiated tumors, it is not an effective treatment for metastatic cancers. Therefore, developing novel and effective treatment strategies for cancer is urgently needed to save patients with distant cancer metastasis. Immunotherapy enhances the body’s own immune system to fight cancer by activating the immune cells, and consequently, to achieve the systemic anticancer effects, and it is considered to be an adjuvant therapy that can enhance the efficacy of particle beam radiotherapy. This review highlights the research progress of the antimetastasis effect and the mechanism of the photon beam or particle beam radiotherapy combined with immunotherapy and predicts the development prospects of this research area.